Ideal Cardiovascular Health Metrics and Incidence of Ischemic Stroke Among Hypertensive Patients: A Prospective Cohort Study - Ying, Yuchen; Lin, Shaoyi; Kong, Fanqian; Li, Yuying; Xu, Shujun; Liang, Xiaofeng; Wang, Changyi; Han, Liyuan (Frontiers in Cardiovascular Medicine, 2020)
Background: This study aimed to assess the the relationship between ideal cardiovascular health (CVH) metrics and incident ischemic stroke (IS) in hypertensive patients, especially those with hyperhomocysteinemia (HHcy). Methods: A prospective cohort study enrolled 5,488 hypertensive patients in Nanshan District of Shenzhen City in southern China from September 2011 to December 2017. CVH metrics were defined according to the American Heart Association. Cox proportional hazards models were used to examine the associations between the number of ideal CVH metrics and the incidence of IS by calculating multivariable-adjusted hazard ratios (HRs) and 95% CI. Results: During an average follow-up of 5.7 years, 340 IS patients were identified. Compared with those having 0 ideal CVH metrics, the HRs (95% CIs) for IS among those with 1, 2, 3, 4, and 5-6 ideal CVH metrics were 0.62 (0.31-1.25), 0.37 (0.19-0.74), 0.37 (0.18-0.74), 0.34 (0.16-0.71) and 0.28 (0.12-0.63), respectively (P trend <0.001). An ideal healthy diet score and ideal fasting blood glucose level were independently associated with IS among participants, with HRs (95% CIs) of 0.53 (0.33-0.86) and 0.32 (0.17-0.66), respectively. Additionally, compared with those with normal total homocysteine (tHcy) levels (<15 μmol/L) , the HR (95% CI) for IS among participants with HHcy and who had 5-6 ideal CVH metrics was 0.50 (0.27-0.92). Conclusion: An increased number of ideal CVH metrics was inversely associated with the incidence of IS in hypertensive patients. The participants with HHcy who had 5-6 ideal CVH metrics exhibited a lower IS risk than those with normal tHcy levels.